Uncontracted core Pople basis sets in vibrational frequency calculations. Issue 22 (1st October 2018) - Hanson‐Heine, Magnus W. D.
Abstract: The effects that uncontracting the core 1 s basis functions in the Pople basis sets have on the calculation of harmonic vibrational frequencies, scaling factors, and anharmonic frequencies are examined for a selection of hybrid and meta‐hybrid density functional theory methods across a wide range of molecules. Median improvements of around half a wavenumber indicate that uncontracting the core functions provides modest improvements for harmonic calculations. The importance of these core functions is found to increase when using meta‐hybrid or anharmonic methods. The core functions are also found to be particularly important for several types of vibrational coordinate, including some carbonyl and carbon‐nitrogen stretching modes, where interaction between the uncontracted 1 s functions and triple‐ζ 2 s functions appear to play a significant role. Extra core functions are also particularly important for anharmonic second‐order perturbation theory calculations involving alkyne molecule bending modes, where individual transitions can change by as much as 230 wavenumbers. Abstract : Pople basis sets are commonly used for anharmonic calculations. Uncontracting the core functions of the Pople basis sets causes a small improvement when calculating vibrational frequencies for most molecules. However, under certain conditions these changes can become quite large and a more careful choice of basis set and calculation method is recommended in these highlighted cases.